[latex]\left \{ {{3y^2 - 2xy = 160;} \atop {y^2 - 3xy - 2x^2=8}} \right[/latex]
[latex]\left \{ {{3y^2 - 2xy = 160;} \atop {y^2 - 3xy - 2x^2=8}} \right[/latex]
Ответ(ы) на вопрос:
3y²-2xy=160 y²-3xy-2x²=8 -2xy=160-3y² y²-3xy-2x²=8 x=-80/y+3y/2 y²-3xy-2x²=8 y²-3(-80/y+3y/2)y-2(-80/y+3y/2)²=8 y²+240-9y²/2-2(6400/y²-240+9y²/4=8 y²+240-9y²/2-12800/y²+480-9y²/2=8 2y⁴+480y²-9y⁴-25600+960y²-9y⁴=16y² -16y⁴+1424y²-25600=0 y⁴-89y²+1600=0 t=y² t²-89t+1600=0 Δ=(-89)²-4*1*1600 Δ=7921-6400 Δ=1521 √Δ=39 t₁=(-(-89)-39)/(2*1) t₁=50/2 t₁=25 t₂=(-(-89)+39)/(2*1) t₂=128/2 t₂=64 y₁²=25 y₁=-5 ∨ y₁=-5 y₂²=64 y₂=-8 ∨ y₂=8 x₁=-80/(-5)+3*(-5)/2 ∨ x₁=-80/5+3*5/2 x₁=16-15/2 ∨ x₁=-16+15/2 x₁=32/2-15/2 ∨ x₁=-32/2+15/2 x₁=17/2 ∨ x₁=-17/2 x₂=-80/(-8)+3*(-8)/2 ∨ x₂=-80/8+3*8/2 x₂=10-12 ∨ x₂=-10+12 x₂=-2 ∨ x₂=2 (17/2,-5),(-17,2,5),(-2,-8),(2,8)
у2 - в квадрате у4- в 4 стапені 3у2-2ху=160 х=(3у2-160)/2у подставим во второе уравнение у2-3*((3у2-160)/2у)*у-2*((3у2-160)/2у)* ((3у2-160)/2у)=8 у2-4.5у2+240-(9у4-960у2+25600)/2у2=8 - домножем на 2у2 2у4-9у4+480у2-9у4+960у2-25600=16у2 пусть у2=а 2а-9а2+480а-9а2+960а-25600=16а упростим -16а2+1424а-25600=0 разделить на -16 а2-89+1600=0 а1=64 а2=25 Тогда у2=64 у1=8 у2=-8 х1= (3у2-160)/2у=(3*8*8-160)/16=2 х2=(3*-8*-8-160)/(-16)=-2 у2=25 у3=5 у4=-5 х3=(3*5*5-160)/10=-8.5 х4=(3*-5*-5-160)/-10=8.5
Не нашли ответ?
Похожие вопросы